2019
DOI: 10.1021/acssuschemeng.9b04149
|View full text |Cite
|
Sign up to set email alerts
|

Role of Two-Electron Defects on the CeO2 Surface in CO Preferential Oxidation over CuO/CeO2 Catalysts

Abstract: Owing to the peculiar synergistic interaction between CuO and CeO 2 at the interface, CuO/CeO 2 is one of the most efficient catalysts to purify a H 2 source, which is used in a proton exchange membrane fuel cell by preferential oxidation (PROX) of CO. The defective structure in CeO 2 is considered to be a crucial factor affecting the synergistic interaction. However, the defect−interaction relationship has not been well established due to the complex variation in different types of defects. Therefore, in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…In Figure 5c, the spectrum with typical six binding energy peaks at 882.1, 898.5, 916.8 eV are in agreement with Ce 4+ in previous report [21] . The 3d 5/2 and 3d 3/2 spin‐orbit components of Ce 4+ are marked in Figure 5c, referring to Ce 4+ v and u spin‐orbit doublets [8,18] . In comparison to pure sample and Ce in CHS (Figure S5c), binding energy Ce3d 5/2 at 882.1 eV and the six peaks overlap well with these of pure sample without any shift, indicating the majority state of Ce in CHS‐CuO are Ce IV oxide.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In Figure 5c, the spectrum with typical six binding energy peaks at 882.1, 898.5, 916.8 eV are in agreement with Ce 4+ in previous report [21] . The 3d 5/2 and 3d 3/2 spin‐orbit components of Ce 4+ are marked in Figure 5c, referring to Ce 4+ v and u spin‐orbit doublets [8,18] . In comparison to pure sample and Ce in CHS (Figure S5c), binding energy Ce3d 5/2 at 882.1 eV and the six peaks overlap well with these of pure sample without any shift, indicating the majority state of Ce in CHS‐CuO are Ce IV oxide.…”
Section: Resultssupporting
confidence: 86%
“…These two typical reflections are characteristic for the presence of Tenoirte (CuO) phase [5c] . The diffraction peaks attributed to CuO are visible, indicating that CuO species are highly dispersed on the surface [8,18] . The peaks are reasonably weak for two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, ethanol washing during the preparation of CuO x /CeO 2 oxides leads to decreased particle sizes, as it affects the dehydration process between precursors particles, resulting in decreased adsorbed water and improved dispersion [272]. Very recently, a novel ultrasound-assisted precipitation method was employed to adjust the defective structure of CeO 2 and in turn, the CO-RPOX activity [273]. By means of characterization techniques and theoretical calculations, it was shown that only two-electron defects on ceria surface (i.e., defects adsorbing oxygen to form peroxides instead of superoxide species which are formed on one-electron defects) were responsible for the formation of Cu + and Ce 3+ species, which were intimately involved in the CO adsorption and oxygen activation processes [273].…”
Section: Preferential Oxidation Of Co (Co-prox)mentioning
confidence: 99%
“…Very recently, a novel ultrasound-assisted precipitation method was employed to adjust the defective structure of CeO 2 and in turn, the CO-RPOX activity [273]. By means of characterization techniques and theoretical calculations, it was shown that only two-electron defects on ceria surface (i.e., defects adsorbing oxygen to form peroxides instead of superoxide species which are formed on one-electron defects) were responsible for the formation of Cu + and Ce 3+ species, which were intimately involved in the CO adsorption and oxygen activation processes [273]. In particular, the adsorption of O 2 on two-electron defects resulted in peroxides formation, followed by Cu ions incorporation towards the development of Cu-O-Ce structure.…”
Section: Preferential Oxidation Of Co (Co-prox)mentioning
confidence: 99%
“…25,26 As reported in several relevant studies, six peaks labeled as V, V″, V‴, U, U″ and U‴ are the evidence of the presence of Ce 4+ , [25][26][27] while other four peaks denoted as V 0 , V′ and U 0 , U′ are assigned to the final Ce 3+ states which can be used as an indicator of the existence of oxygen vacancies. 14,25,28 The increase of the intensity of V 0 and U 0 peaks indicates the increase of Ce 3+ content on the surface of CeO 2 . The surface composition has been also confirmed by XPS quantitative analysis shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%